Serum Neudesin Levels in Patients with Congenital Hypothyroidism - Semra Bahar; İlker Tolga Özgen; Yaşar Cesur; Caner Yıldız; Ömer Faruk Özer; Emel Hatun Aytaç Kaplan; Zümrüt Kocabey Sütçü (JCRPE)
Objective: Neudesin is a newly discovered protein mainly secreted from adipose tissue and the brain. It plays a role as a neurotrophic factor in the brain and a negative regulator of energy expenditure. Neurodevelopmental delay and cognitive dysfunction are common features in cases with congenital hypothyroidism (CH) without treatment. Given the role of neudesin in brain development and its contribution to the survival of mature neurons, the relationship between neudesin and thyroid hormone was evaluated in babies diagnosed with CH. Methods: Babies aged between 2-4 weeks and diagnosed with CH and healthy controls of similar age were included. All patients were evaluated for thyroid hormones and plasma neudesin levels. The basal neudesin levels between the patient and control groups and the patients’ neudesin levels before and after l-thyroxine treatment were compared. Results: Fifty-two babies [32 with CH, 14 (44%) female, aged 19±7 days and 20 healthy controls, 7 (35%) female, aged 22±8 days] were included. There was no significant difference in baseline neudesin between the CH and control groups (6.77±6.41 vs. 7.93±7.04 ng/mL, respectively; p=0.552). However, neudesin levels increased significantly following one month of therapy in the CH group [median: 3.93 (minimum: 0.31, maximum: 30.06) vs. median: 6.15 (minimum: 2.17, maximum: 70.05) ng/mL, p=0.019]. Conclusion: Although there was no difference in baseline neudesin levels between the patient and control groups, neudesin levels increased after short-term treatment. Larger prospective studies are needed to understand the pathophysiological role of neudesin in untreated and treated early CH.